Africa risen : a new era of speculative fiction - Thomas, Sheree R.; Ekpeki, Oghenechovwe Donald; Knight, Zelda (Tom Doherty Associates, 2022)
"From award-winning editorial team Sheree Renée Thomas, Oghenechovwe Donald Ekpeki, and Zelda Knight comes an anthology of thirty-two original stories showcasing the breadth of fantasy and science fiction from Africa and the African Diaspora. A group of cabinet ministers query a supercomputer containing the minds of the country's ancestors. A child robot on a dying planet uncovers signs of fragile new life. A descendent of a rain goddess inherits her grandmother's ability to change her appearance-and perhaps the world. Created in the legacy of the seminal, award-winning anthology series Dark Matter, Africa Risen celebrates the vibrancy, diversity, and reach of African and Afro-Diasporic SFF and reaffirms that Africa is not rising-it's already here"--